Legal Education Regarding the Dangers of Narcotics Abuse Among Adolescents in Senganan Village - Ni Nyoman Juwita Arsawati; Komang Febriana (Universitas Negeri Semarang, 2023)
Drugs are a new style of colonialism in this millennial era, because the target is productive young generations. Drug abuse is the biggest threat to the nation's young generation. The importance of counseling and guidance related to the impact of drug abuse among the community, especially teenagers, in order to protect the younger generation, we need to increase it. This counseling is intended as knowledge for teenagers about the types of drugs and the dangers of drugs for themselves. The effect of counseling on the dangers of drug abuse in adolescents is very large because it can prevent teenagers from being influenced into promiscuity so that they can create the next generation of superior nations.